Risks Facing Russian Stock Exchange during Sanctions and Ways of their Overcomin - A. P. Garnov; E. V. Afanasyev; N. P. Tishkina (Вестник Российского экономического университета имени Г. В. Плеханова)
The article deals with problems facing Russian stock exchange in conditions of sanctions imposed by western states on organizations and individuals of the Russian Federation. They are harmful and affect key financial institutions of Russia, thus they are bound to impact the stock market experiencing turbulence since late February 2022. In order to cut the adverse influence of such measures both the government and the regulator (the Central Bank of the Russian Federation) have to response by tough decisions aimed at stabilizing the situation in finance sphere, among which we should mention a sharp rise in the key interest rate, closing stock trading on the Moscow exchange, restrictions on foreign currency transactions and interventions on stock market. The article highlights problems that caused serious fluctuations of currency rate on commodity and foreign exchange markets brought about by unstable political situation in the world. The authors evaluated prospects of further movements of market and possible countermeasures, which should be taken both by the Russian government and the regulator to smooth negative after-effects in country economy.